1993
DOI: 10.1002/bjs.1800801241
|View full text |Cite
|
Sign up to set email alerts
|

Change towards earlier stage at presentation of colorectal cancer

Abstract: A study was carried out to investigate the change in stage at presentation of patients with colorectal cancer over 10 years. Cases were identified from the control group of subjects enrolled into a randomized controlled study based on Haemoccult screening for colorectal neoplasia. Of 405 subjects in the control group (presenting with symptomatic colorectal cancer, 206 presented before 1989 and 199 since then. The number of patients with Dukes' stage A carcinoma diagnosed since 1989 rose from 21 (10.4 per cent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…25 The use of imaging techniques improved the identification rate for early stage rectosigmoid tumors (from 9.9% to 28%), but not colon carcinoma. 26 Currently available diagnostic modalities (barium enema, CT, X-ray study, MRI, endorectal ultrasonography, Doppler ultrasonography, and immunoscintigraphy) have limited value in the preoperative diagnosis of tumor invasion of the bladder, 27,28 although these methods can help evaluate patients believed to have recurrent tumors. 27,29 However, in our study, when both intraoperative examination and CT scan indicated tumor involvement of the bladder, Ͼ90% of such patients had pathologic involvement of the bladder at the time There was no significant difference between the two groups (P ϭ 0.258, log rank test).…”
Section: Discussionmentioning
confidence: 99%
“…25 The use of imaging techniques improved the identification rate for early stage rectosigmoid tumors (from 9.9% to 28%), but not colon carcinoma. 26 Currently available diagnostic modalities (barium enema, CT, X-ray study, MRI, endorectal ultrasonography, Doppler ultrasonography, and immunoscintigraphy) have limited value in the preoperative diagnosis of tumor invasion of the bladder, 27,28 although these methods can help evaluate patients believed to have recurrent tumors. 27,29 However, in our study, when both intraoperative examination and CT scan indicated tumor involvement of the bladder, Ͼ90% of such patients had pathologic involvement of the bladder at the time There was no significant difference between the two groups (P ϭ 0.258, log rank test).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the results of the trials can be translated into the general population there is an opportunity to have a positive impact on mortality from colorectal cancer now, and this must be taken seriously. Also, experience from the Nottingham study indicates that there may be important beneficial sequelae; stage at presentation may be improved even in those who do not have their tumours detected by screening 8 and screening may reduce the proportion of tumours presenting as emergencies. 20 Furthermore, estimates of cost per quality adjusted life-year gained from colorectal screening show it to be similar in cost eVectiveness to breast cancer screening in the short term and better in the long term 21 .…”
Section: Accuracy Of the Testmentioning
confidence: 99%
“…For example, during the Nottingham study, the stage of presentation of rectal cancer markedly improved in the control group, presumably because of an educational eVect. 8 It is also of interest that the dramatic drop in breast cancer mortality recently found from registry data from the United Kingdom and the United States 9 coincides with the introduction of widespread screening for the disease. Although this drop cannot be attributed to screening alone, it can be argued that screening and its associated quality assurance has acted as a stimulus for improving both clinical standards and population awareness, leading to earlier presentation and more eVective management.…”
Section: Challenges For the Pilot Trialmentioning
confidence: 99%
“…This minimally invasive technique allows for the precise excision of tumors in the rectum [1,5,11,13,18]. Due to recent improvements in diagnostic accuracy, more early-stage rectal cancers are now treated [10,16]; therefore, local therapy using TEM is expected to play an increasingly important role in the management of rectal cancer.The incidence of synchronous cancer of the colorectum has been reported to range between 1.5% and 7.6% [3,9,15]. If one of the tumors in patients with synchronous colorectal cancer is T1 rectal cancer according to the TNM classification [12], excision of the rectal lesion via TEM will reduce the number of unnecessary radical operations, such as low anterior resection or abdominoperineal resection.…”
mentioning
confidence: 99%
“…This minimally invasive technique allows for the precise excision of tumors in the rectum [1,5,11,13,18]. Due to recent improvements in diagnostic accuracy, more early-stage rectal cancers are now treated [10,16]; therefore, local therapy using TEM is expected to play an increasingly important role in the management of rectal cancer.…”
mentioning
confidence: 99%